الكفاية الذاتية وعلاقتها بالضغوط المدركة لدى عينة من الطالبات المتزوجات والعازبات في كلية التربية بجامعة تشرين (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
هدف البحث إلى معرفة العلاقة بين كفاية الذات والضغوط المدركة لدى الطالبات (العازبات والمتزوجات) في كلية التربية بجامعة تشرين، والتعرف إلى الفروق بينهن في كل من الكفاية الذاتية والضغوط المدركة، ومستوى هاتين المتغيرتين باستخدام مقياسي الكفاية الذاتية العامة  (Schwarzer & Jerusalem,1989) والضغوط المدركة(Cohen et al., 1983) . وطبق البحث خلال الفصل الأول من العام الدراسي 2012- 2013، على عينة بلغت370) ) طالبة عازبة ومتزوجة. وتم التأكد من الثبات بتطبيقها على عينة استطلاعية شملت (40) طالبة من خلال حساب معامل ألفا كرونباخ، والذي بلغ (0.7)، لمقياس الضغوط المدركة، (0.82)، لمقياس الكفاية الذاتية، كما بلغ معامل الارتباط (0.61)، (0.83)، للمقياسين على التوالي بطريقة الاختبار وإعادة الاختبار. وللوصول إلى نتائج البحث، استُخدمت النسب المئوية، والمتوسطات الحسابية، ومعامل الارتباط بيرسون. بيّنت النتائج أن مستوى الضغوط المدركة مرتفع لدى الطالبات المتزوجات ومنخفض لدى العازبات، في حين ظهر مستوى الكفاية الذاتية مرتفعاً لدى الطالبات العازبات، ومنخفضاً لدى المتزوجات. وأظهرت النتائج وجود ارتباط سلبي بين الضغوط المدركة والكفاية الذاتية لدى أفراد عينة البحث. كذلك أظهرت النتائج وجود فروق دالة بين الطالبات العازبات والمتزوجات في الكفاية الذاتية لصالح العازبات، ووجود فروق دالة بين الطالبات العازبات والمتزوجات في الضغوط المدركة لصالح المتزوجات. كما أوصى البحث بضرورة إقامة ندوات إرشادية لتوعية الطالبات المتزوجات حول أساليب مواجهة الضغوط، وإجراء مزيد من البحوث في هذا المجال على عينات مختلفة. This study is directed to discover the relationship between self-efficiency and the perceived stresses among single and married female students in the Faculty of Education at Tishreen University, and recognizing the differences of self-efficiency and perceived stresses among them and the level of these two variables using the self-efficiency scale and perceived stresses scale. This was applied on (370) students for the academic year 2012/2013. It was proved by applying it on an experimental sample of (40) students. Reliability was established through Cronbach–Alpha, which reached (0.7) for perceived stresses scale and (0.82) for self-efficiency scale. The correlation coefficient reached (0.61) and (0.83)  for the two scales respectively via testing and retesting. The following statistical methods were used: percentage, averages, Pearson's correlation coefficient. The results showed the level of perceived stresses was high among married students, and low among single ones, and that the level of self-efficiency was high among single students, and low among married ones. In addition, the results showed that there was a negative correlation between self-efficiency and perceived stresses in the sample. Moreover, there were statistically significant differences between married and single students as to self-efficiency in favor of the single, and statistically significant differences between married and single students as to perceived stresses in favor of the married ones.